Problem Pemaknaan Al-Quran Dalam Metode Tafsir Konvensional - Irham Irham (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Problems with the Meaning of the Al-Quran in Conventional Interpretation MethodsThis article explores the deviations in meaning in the interpretation of the Qur'an resulting from the use of conventional methods of interpretation, and what causes these deviations. This study is a literature review using descriptive-analytical method. The findings indicate that the interpretation resulting from the use of conventional interpretation methods has causes that make the results of the interpretation of the Koran deviate. There are two categories of causes, namely; underlying causes and specific causes. The basic cause of the deviation occurs because the requirements and standards for interpretation are not fulfilled optimally and consistently. The causes specifically for these deviations are related to the factors of interpretation deviation in the al-ma'tsur, al-ra'yu and al-isyari approaches. Knowledge of the causes of deviations in the meaning of the Qur'an can be a separate part of conventional interpretation methods